Effects of substrate temperatures on the thermal stability of AlxOy/Pt/AlxOy multilayered selective solar absorber coatings. (March 2015) - Nuru, Z.Y.; Arendse, C.J.; Mongwaketsi, N.; Gohshal, S.K.; Nkosi, M.; Maaza, M.
Abstract: We report the effects of substrate temperatures on the thermal stability of Al x O y /Pt/Al x O y multilayered selective solar absorber coating (MSSAC). The samples were deposited at different substrate temperatures (from room temperature up to 250 °C), and then annealed at various temperatures (300–600 °C) in air for 2 h. Characterizations are made via X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS), Atomic Force Microscopy (AFM), Raman Spectroscopy, UV–Vis and emissometeric measurements. These coatings were found to be thermally stable up to 500 °C with good spectral selectivity of 0.930/0.11. Furthermore, the observed decrease in the spectral selectivity 0.883/0.13 at 600 °C is attributed to the diffusion of Cu and the formation of CuO phase. Such phase formation was confirmed using XRD and Raman spectral analysis. The insensitiveness of the thermal stability of such coatings on the substrate temperature is demonstrated. Highlights: Al x O y /Pt/Al x O y solar absorber deposited at different substrate temperatures. The thermal stability of Al x O y /Pt/Al x O y solar absorber coatings was not affected. Al x O y /Pt/Al x O y solar absorber was thermally stable in air up to 500 °C for 2 h. Particle size and roughness increased at elevated substrate temperature.